Management of traumatised maxillary central incisor with immature open apex using mineral trioxide aggregate and tailor made gutta percha: a case report - Patil, Suvarna; Hoshing, Upendra; Kambale, Sharanappa; Gupta, Ruchika (International Journal of Research in Medical Sciences, 2017)
Root development and apex closure after the eruption of teeth takes a minimum of 3-4 years. If trauma to the pulp occurs during this period, it becomes a challenge for the clinician to treat the pulpal injury. Apexification is the treatment of choice for necrotic teeth with immature apex. Apexification done with calcium hydroxide encounters certain difficulties like very long treatment time, possibility of tooth fracture and incomplete calcification of the bridge. Mineral trioxide aggregate (MTA) was introduced as an alternative material to traditional materials for the apexification of immature permanent teeth. This case report presents successful management of a case with open apex using MTA followed by Tailor made gutta-percha.